The Relationship between Body Composition and Anaerobic Capacity of Female Futsal Players - Asep Sumpena; Yunyun Yudiana; Dikdik Zafar Sidik; Amung Ma'mun (Universitas Pendidikan Indonesia, 2022)
Measurement of Body Composition (BC) is carried out for various purposes, such as uniting the growth and development of athletes and determining motor performance, physical activity, changes in body composition, as well as nutritional interventions. This study aimed to determine the relationship between Body Composition (BC) and anaerobic ability of female futsal players aged 17-19 years. Twenty female futsal players participated in this study. Muscle mass, Body Mass Index (BMI), Body Fat Percentage, Water Percentage, Protein Percentage, Basal Metabolism, Visceral Fat, and Bone Mass were measured to determine the fat percentage of bone, air, and muscle in the body. Measurement of body composition was also intended to detect the food intake needed by the body and obtain information relevant to disease prevention and treatment. The Running Based Anaerobic Sprint Test (RAST) was conducted to measure the anaerobic endurance. The research method used was a descriptive correlation with a quantitative approach. The finding showed no correlation between Running Based Anaerobic Sprint and Body Fat Percentage, Water Percentage, Protein Percentage, Basal Metabolism, and Visceral Fat. However, there was a positive relationship between Muscle Mass, Body Mass Index (BMI), Bone Mass of the samples, and their Running Based Anaerobic Sprint (p0.05). It concludes that the score of Muscle mass, Body Mass Index (BMI), and Bone Mass affected the anaerobic capacity of female futsal players aged 17-19 years. The normal status of body composition and body fat percentage can be maintained through maintaining consumption patterns and increasing physical activity.